Modifying and Pilot Testing the Pap Smear Belief Questionnaire. (9th December 2014) - Ackerson, Kelly; Doane, Lisa Stines; McNutt, Robert; Shao, Yuanyuan
This study is a report on modifications and pilot testing of a measurement tool to predict Pap testing based on the Interaction Model of Client Health Behavior. Women have been found to avoid routine cervical cancer screening (CCS) due to personal influencing factors. For this study, the Pap Smear Belief Questionnaire (PSBQ) was modified by adding items and evaluated through content validity index (CVI = .89) and cognitive interviews (think-aloud protocol), resulting in a 31-item instrument with four subscales (Benefits, Barriers, Vulnerability, Experiences). Pilot testing the modified PSBQ was conducted at a local agency. Fifty-three women completed and returned the PSBQ, which had good internal consistency, with a Cronbach's alpha coefficient of .81 (Benefits α = .51; Barriers α = .85; Vulnerability α = .78; Experiences α = .87). Test–retest reliability of the 31-item PSBQ was also good (.878). Univariate logistic regression indicated that the only significant predictor of seeking/avoiding routine screening by women's background characteristics was social influence ( p = .04). Subscales found to be significant predictors in Pap testing were Barriers ( p = .003) and Gynecological Exam Experiences ( p = .04). The refined 31-item PSBQ has good psychometric data supporting its use in predicting CCS. However, this research should be replicated in a larger sample enabling further validity and reliability testing of the PSBQ. Understanding women's attitudes toward CCS will help health care providers, who deal with gynecological health, develop more effective screening programs and interventions facilitating better experiences for women contributing to an increase in routine screening.